Dynamic 18F-FDOPA PET Findings After Carbidopa Premedication in 2 Adult Patients With Insulinoma-Related Hyperinsulinemic Hypoglycemia. (August 2015) - Imperiale, Alessio; Bahougne, Thibault; Goichot, Bernard; Bachellier, Philippe; Taïeb, David; Namer, Izzie Jacques
Abstract : Abstract: 18 F-fluorodihydroxyphenylalanine (FDOPA) PET seems to be of limited value to localize pancreatic insulin–secreting tumors in adult with hyperinsulinemic hypoglycemia. Carbidopa is an efficient inhibitor of the peripheral aromatic amino acid decarboxylase, significantly reducing the physiological pancreatic FDOPA uptake. Nevertheless, carbidopa effect on FDOPA uptake in insulinomas is not fully elucidated. No final consensus has been reached about the usefulness of carbidopa in patients with insulinoma-related hyperinsulinemic hypoglycemia. Moreover, the ideal timing for PET/CT acquisitions is a matter of discussion. We report the results of dynamic FDOPA PET performed after carbidopa premedication in 2 adult patients with insulinoma.